Emprego de diretrizes sustentáveis nos projetos de engenharia de uma residência em Nísia Floresta/RN - Ribeiro, Marília Nunes Freire (Universidade Federal Rural do Semi-Árido, 2018)
The search for sustainable buildings, which bring less impact to the environment, goes through architectural and engineering projects, always aiming at the elaboration of real estate with maximum reuse of gray water and sanitary basin and minimum consumption of drinking water. Thus, the present thesis has the objective of elaborating the rainwater, sanitary sewage and cold water projects of a residence in Nísia Floresta, proposing ideas of low cost of reuse, dimensioning the hydraulic systems and studying their feasibility, proposing changes in the original architectural project and suggesting alternatives to the problems encountered during project design. Initially, using AutoCAD and Sketchup, the pluvial water pipes were launched and the viability of reuse implantation was studied in 3 points of the residence. The washing machine, which will be supplied by this precipitation of rain and cold water, will generate a saving of 2,400 liters of water per month. In the sewage project, the effluent from the toilet will feed an evapotranspiration tank, avoiding contamination of the water table and constantly irrigating banana trees, papaya trees or other plants placed on this tank. The gray water will irrigate banana trees, nourishing the soil with nutrients necessary for this fruit tree. In the bathroom there will be reuse of the water from the lavatory in the attached boxes. The cold water project will come to complement the places that are reused and supply the other points of use of the residence, being places in which there is direct contact of the user with the water. In general, it was observed that the use of rainwater and reuse of lavatory water reflects the reduction of drinking water consumption by 20.9%, without considering the water reused for garden watering. In addition, the evapotranspiration basin and the re-use of gray water will result in beneficial nutrients for the trees and plants sown on site.
Monografia
Keywords: Sustentabilidade; Projetos de complementares; Reúso de água; ENGENHARIAS::ENGENHARIA CIVIL